2022
DOI: 10.1037/pro0000456
|View full text |Cite
|
Sign up to set email alerts
|

Glass ceiling versus sticky floor, sideways sexism and priming a manager to think male as barriers to equality in clinical psychology: An interpretive phenomenological analysis approach.

Abstract: The profession of clinical psychology is predominantly populated by women, yet women are significantly underrepresented in the higher levels of the profession. The aim of this study was to explore the perceptions and experiences of gender difference and implicit bias within the profession of clinical psychology. Through 16 semistructured interviews with psychologists at four different trajectories of their clinical psychology career (10 assistant psychologists, 2 clinical trainees, 3 qualified clinicians, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Research has also found that women are more likely than men to lack confidence in their ability to fulfil professional roles and competencies (Cech et al 2011) and be averse to self-promotion (Broughton and Miller 2009). Additionally, participant narratives revealed interpersonal gender and race-deviance penalties, consistent with research and reflecting societal discourses of dominant masculinities and submissive femininities (Williams et al 2013;Berdahl et al 2018;Reynolds et al 2022): women who performed masculine competition and confidence could be resented and "not liked," which may have been exacerbated by stereotypes of submissive, modest or shy Asian women (Dodds 2012); while men could be more stigmatized than women for deviating from masculine confidence and extroversion by performing feminine quietness.…”
Section: Think They Value Commitment and Hard Workmentioning
confidence: 53%
See 3 more Smart Citations
“…Research has also found that women are more likely than men to lack confidence in their ability to fulfil professional roles and competencies (Cech et al 2011) and be averse to self-promotion (Broughton and Miller 2009). Additionally, participant narratives revealed interpersonal gender and race-deviance penalties, consistent with research and reflecting societal discourses of dominant masculinities and submissive femininities (Williams et al 2013;Berdahl et al 2018;Reynolds et al 2022): women who performed masculine competition and confidence could be resented and "not liked," which may have been exacerbated by stereotypes of submissive, modest or shy Asian women (Dodds 2012); while men could be more stigmatized than women for deviating from masculine confidence and extroversion by performing feminine quietness.…”
Section: Think They Value Commitment and Hard Workmentioning
confidence: 53%
“…Research finding that white, male-dominated senior managers have promoted employees in their own image, suggests that such practices can increase conscious and unconscious bias's influence and undermine equality and diversity (Broughton and Miller 2009;Reynolds et al 2022). Moreover, extreme and conformant characteristics (Section 3.3) of "well-liked" employees who were rewarded with pre-determined promotions (Section 3.2.5), contributed to organizational inequality regimes.…”
Section: Beneficence For But Subject To Growthmentioning
confidence: 99%
See 2 more Smart Citations